Serum Calprotectin Level in Type 2 Diabetic Patients with and without Diabetic Peripheral Neuropathy: A Comparison Study - Israa Abdelmalik Salem; Sura Ahmed Abdulsattar; Haider Fadhil Alrubaye (Mustansiriya Medical Journal)
Background: Peripheral neuropathy is one of the microvascular complications that affects patients with diabetes mellitus and involves both sensory and motor nerves. The development and the progress of diabetic peripheral neuropathy (DPN) were ascribed to the inflammatory activity of the immune cells in the nerves. Calprotectin (CLP) is a heterodimer protein found in the membranes of monocytes and other inflammatory cells and the cytosol of neutrophils and released from them up to activation. Aim of Study: Evaluation of serum CLP level as a potential inflammatory biomarker for the occurrence of DPN in type 2 diabetic patients. Patients and Methods: one hundred and twenty-six patients diagnosed with type 2 diabetes mellitus were randomly selected from those who attended the National Diabetic Center between December 2022 and July 2023. Michigan Neuropathy Screening Instrument (MNSI) and nerve conduction study (NCS) were used for grouping the patients. Enzyme-linked immunosorbent assay technique has been used to measure serum CLP levels. Results: Serum levels of CLP showed no significant differences among patients with and those without diabetic peripheral neuropathy according to their NCS findings and the total scores for each and for both in combination according to the subgroups (P > 0.05). Conclusions and Recommendations: The serum level of CLP in type 2 diabetic patients was not affected by the occurrence of diabetic peripheral neuropathy. Further studies are required on newly diagnosed patients and a larger sample size.